Pre/post-rake diversity combining for UWB communications in the presence of pulse overlap - Cheng, Xiantao (2013)
Taking the effect of pulse overlap into account, we address the pre/post-rake technique using rake structure at both transmitter and receiver. Firstly, we propose a single-stream (SS) pre/post-rake, in which the pair of pre-rake and post-rake weighting vectors is optimally derived through generalized eigenvalue decomposition (GEVD). Secondly, by judiciously designing multiple pairs of weighting vectors, we derive multiple-stream (MS) pre/post-rake, which enables parallel subchannel transmission while not requiring multiple antennas at the transmitter or receiver. Finally, we conduct simulations to verify the advantages of the SS pre/post-rake and the MS pre/post-rake over existing rakes.